DAMPAK BANTUAN INDONESIA TERHADAP NEGARA ANGGOTA KERJA SAMA SELATAN-SELATAN DI KAWASAN ASIA - Ayu Rachmawaty,A Ade Rachmaliani, Ahmad Rizaldi (Mandala: Jurnal Ilmu Hubungan Internasional, 2019)
South South Cooperation (SSC) is a form of development cooperation between developing countries based on the principle of solidarity, equality (mutual opportunity) and the principle of mutual benefit. Indonesia is one of the member countries of Cooperation which is active as a foreign aid provider for SSC partner countries. So far, the available discussions have only focused on the benefits of South South Cooperation (SSC) on Indonesia's national interests. This journal examines from another perspective on the impact of Indonesia's foreign assistance on the development of member states of South South Cooperation. The research method used was descriptive qualitative with a focus on providing assistance in the Asian region. Foreign aid provided by Indonesia focuses more on training and community empowerment programs. Indonesia also provided financial assistance but the value was no greater than non-financial assistance worth US $ 60 million. In addition, Indonesia's foreign aid for conflict countries in Asia includes educational, economic, health and social programs that aim to help and alleviate the suffering of people in the midst of conflict. The impact of the provision of non-financial assistance is that people in developing countries in Asia get new knowledge, skills and information to be implemented in their countries and increase community empowerment so that they are not increasingly dependent on foreign financial assistance.